The effect of heating rate on the phase transformation of Ni/Ti multilayer thin films. (May 2017) - Cavaleiro, A.J.; Ramos, A.S.; Martins, R.M.S.; Braz Fernandes, F.M.; Vieira, M.T.
Abstract: Ni/Ti multilayer thin films prepared by dual cathode magnetron sputtering were annealed in vacuum at different heating rates. The structural evolution of the multilayer thin films with nanometric modulation periods was studied in-situ by x-ray diffraction using synchrotron radiation. Independently of the multilayer period, a single step rapid reaction occurs at temperatures above 300 °C with the formation of the B2-NiTi austenite phase. The transformation temperature is inversely proportional to the multilayers period (higher temperature for shorter period - 12 nm) and to the heating rate (lower temperature for faster heating rates). Highlights: Phase evolution of Ni/Ti nanomultilayers was followed using synchrotron XRD. Three different stages were identified: phase detection, grain growth, stabilization. The reaction temperature depends on the multilayer period and heating rate. The faster the heating rate, the lower the reaction temperature.